Gestational zinc deficiency impairs brain astrogliogenesis in rats through multistep alterations of the JAK/STAT3 signaling pathway - Supasai, Suangsuda (Redox Biol, 2021)
We previously showed that zinc (Zn) deficiency affects the STAT3 signaling pathway in part through redox-regulated mechanisms. Given that STAT3 is central to the process of astrogliogenesis, this study investigated the consequences of maternal marginal Zn deficiency on the developmental timing and key mechanisms of STAT3 activation, and its consequences on astrogliogenesis in the offspring. This work characterized the temporal profile of cortical STAT3 activation from the mid embryonic stage up to young adulthood in the offspring from dams fed a marginal Zn deficient diet (MZD) throughout gestation and until postnatal day (P) 2. All rats were fed a Zn sufficient diet (control) from P2 until P56. Maternal zinc deficiency disrupted cortical STAT3 activation at E19 and P2. This was accompanied by altered activation of JAK2 kinase due to changes in PTP1B phosphatase activity. The underlying mechanisms mediating the adverse impact of a decreased Zn availability on STAT3 activation in the offspring brain include: (i) impaired PTP1B degradation via the ubiquitin/proteasome pathway; (ii) tubulin oxidation, associated decreased interactions with STAT3 and consequent impaired nuclear translocation; and (iii) decreased nuclear STAT3 acetylation. Zn deficiency-associated decreased STAT3 activation adversely impacted astrogliogenesis, leading to a lower astrocyte number in the early postnatal and adult brain cortex. Thus, a decreased availability of Zn during early development can have a major and irreversible adverse effect on astrogliogenesis, in part via multistep alterations in the STAT3 pathway.